2022
DOI: 10.1371/journal.pone.0263091
|View full text |Cite
|
Sign up to set email alerts
|

Burden and risk factors for antenatal depression and its effect on preterm birth in South Asia: A population-based cohort study

Abstract: Introduction Women experience high rates of depression, particularly during pregnancy and the postpartum periods. Using population-based data from Bangladesh and Pakistan, we estimated the burden of antenatal depression, its risk factors, and its effect on preterm birth. Methods The study uses the following data: maternal depression measured between 24 and 28 weeks of gestation using the 9–question Patient Health Questionnaire (PHQ-9); data on pregnancy including an ultrasound before 19 weeks of gestation; d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Undeniably, looking into the factors that may be connected to an increased propensity for prenatal depression and anxiety is of crucial interest, owing to the fact that mental disorders during pregnancy may impact maternal/infant health adversely, by generating substantial mortality rates and serious morbidities (e.g., increased risk of addictions in pregnancy, obstetrical complications, preterm birth, compromised postpartum bonding, psychological and neurodevelopmental disturbances in children, as well as malnutrition, growth impairment, and infectious/diarrheal diseases; as infants are highly dependent on their mothers for physical care and social interaction) [ 9 , 33 39 ]. A thorough comprehension of the underlying risk factors may enlighten the path towards further refining the identification of maternal mental disorders and enhancing prevention programs in Lebanon.…”
Section: Introductionmentioning
confidence: 99%
“…Undeniably, looking into the factors that may be connected to an increased propensity for prenatal depression and anxiety is of crucial interest, owing to the fact that mental disorders during pregnancy may impact maternal/infant health adversely, by generating substantial mortality rates and serious morbidities (e.g., increased risk of addictions in pregnancy, obstetrical complications, preterm birth, compromised postpartum bonding, psychological and neurodevelopmental disturbances in children, as well as malnutrition, growth impairment, and infectious/diarrheal diseases; as infants are highly dependent on their mothers for physical care and social interaction) [ 9 , 33 39 ]. A thorough comprehension of the underlying risk factors may enlighten the path towards further refining the identification of maternal mental disorders and enhancing prevention programs in Lebanon.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of depressive and anxiety symptomatology during pregnancy have been associated with obstetric problems and adverse pregnancy consequences, such as preterm birth [98]. A recent population-based, cohort survey indicated that women's antenatal depression was related to an increased risk of pregnant women's perinatal depressive symptoms [99]. A meta-analysis further confirmed a significant risk of preterm birth in women with perinatal depression [56].…”
Section: Discussionmentioning
confidence: 99%
“…When examining preterm birth from an evolutionary perspective, it is suggested that adverse maternal contextual factors (e.g., socio-economic status, chronic stress) may initiate adaptive responses that, in conjunction with psychosocial distress, may determine the trajectory of preterm birth [ 75 ]. The risk of preterm birth has been reported to increase when depression occurs in combination with other etiological contributing factors (e.g., parity, household socio-economic status) [ 76 ]. Our study identified four potential effect modifiers: income, food availability, social support from family, and current planned pregnancy.…”
Section: Discussionmentioning
confidence: 99%